Effect of protein oxidation in meat and exudates on the water holding capacity in bighead carp (Hypophthalmichthys nobilis) subjected to frozen storage. (15th February 2022) - Liu, Yueyue; Zhang, Longteng; Gao, Song; Bao, Yulong; Tan, Yuqing; Luo, Yongkang; Li, Xingmin; Hong, Hui
Highlights: Structural changes in myofibers induced by frozen storage caused the decrease of WHC. The oxidation rate of thawing exudates was different from MPs. Oxidation, di-oxidation, and HNE and MDA adduction were major modifications in MPs. Oxidation of MPs decreased WHC by changing configuration and polarity of MPs. Abstract: This study aimed to investigate the effect of myofiber changes and protein oxidation on water holding capacity (WHC) of bighead carp fillets stored at −20 °C. WHC, microstructure, protein oxidation parameters, and specific modifications of oxidized amino acids were analyzed during 9 months of frozen storage. Results indicated that WHC decreased accompanied by myofibers' structural changes (including the formation of cavities among myofibers, breakage of myofibrils and myofibers, and shortening of sarcomeres) and protein oxidation. SDS-PAGE and carbonyl and sulfhydryl content determination of myofibrillar proteins and exudates gave a detailed description of the protein oxidation. LC-MS/MS analysis demonstrated that oxidation, di-oxidation, and 4-hydroxy-2-nonenal (HNE) and malondialdehyde (MDA) adduction were the top four oxidative modifications of proteins. Oxidative modifications impaired configuration and polarity of proteins, which may further affect WHC. This study provides plausible explanations to support the role of protein oxidation in the decrease of WHC in frozen fillets.